Examination of the czech language for permanent residence with focus on vietnamese applicants - Geppert, Ondrej (Bohemica Olomucensia, 2021)
The Examination of the Czech Language is a milestone on the path to gaining permanent residence in the Czech Republic for many non-EU residents. In this paper, the Language Examination is regarded in its formal, contentual, and contextual aspects from an experience-based perspective. In the beginning, the topic of administration and language methodology regarding crucial points in preparation and processing of the Exam is emphasized. The requirements of Czech and European language policy (from which the Examination is derived) are mentioned, and specific attention is paid to the oral section of the Exam as assessing the most significant language skill - speaking. In a later section, the set of the statistical data of the Exam and its results are analyzed where research findings amplify these data. The results show some unfavorable outcomes among a highly variable success rate. Testing and evaluation of the Exam are framed in the linguistic and socio-cultural context, and the potential of the Exam specifically for the integration of the Vietnamese applicants behind the monitored data and processes is illustrated. The lack of systematic language learning was detected as the main limitation of integration and overall perception of the importance of the exam among these foreign residents.
Keywords: Czech Language Examination; Czech Republic; Integration; Language Policy; Vietnamese